Precompactness of the set of trajectories of the controllable system described by a nonlinear Volterra integral equation - Huseyin, Anar; Huseyin, Nesir (Mathematical Modelling and Analysis, 2012)
In this paper the controllable system whose behaviour is described by a nonlinear Volterra integral equation, is studied. The set of admissible control functions is the closed ball of the space L p (p > 1) with radius µ 0 and centered at the origin. It is shown that the set of trajectories of the system is a bounded and precompact subset of the space of continuous functions.